Taxonomy of the Subtribe Maxillariinae (Orchidaceae, Vandoideae) revised - Szlachetko, Dariusz L.; Sitko, Magdalena; Tukałło, Piotr; Mytnik-Ejsmont, Joanna (Biodiversity: Research and Conservation, 2012)
A new classification of the subtribe Maxillariinae (Orchidaceae) is proposed. Thirty-seven genera are revised. The Camaridium group is divided into seven genera, Adamanthus, Camaridium, Pseudomaxillaria, Psittacoglossum and three described here: Chaseopsis, Chelyella and Viracocha. Ornithidium s.l. is divided into seven genera: Heterotaxis, Laricorchis,Neo-urbania, Nitidobulbon, Ornithidium, Vazquezella and Aucellia, the latter two described here. 193 new combinations on the species level are validated and the relationships among the genera are briefly discussed. A key to the determination of all genera representing Maxillariinae s. s. is provided.